Buku Al-Arabiyyatu Bayna Yadaik (Analisis Pengajaran Bahasa Arab Dalam Perspektif Lintas Budaya) - Siti Rohmah Soekarba (Indonesian Journal of Arabic Studies, 2019)
The purpose of this paper is to analyze Arabic teaching methods at the Faculty of Cultural Sciences, University of Indonesia, which uses the book Al-Arabiyyatu bayna Yadaik in the perspective of Cross Cultural Understanding which is assumed to reduce stagnation in conversation and respect for other people's culture by selecting textbooks used as handbooks . Arabic is a reflection of Arabic culture. Three approaches in teaching Arabic are through language, psychology, and sociolinguistics (culture). The teaching of Arabic culture can be applied through listening, conversation, reading and writing material. The research method used is a descriptive qualitative analysis. The conclusion of this article is that the book Al-Arabiyyatu bayna Yadaik displays four competencies, namely listening skills (maharatu al-istima'), reading (maharatu al-qira'ah), speaking (maharatu al-kalam), and writing (maharatu al-kitabah), in addition to additional knowledge in the form of language about Arabic and Islamic culture that can be used as an alternative to cross-cultural Arabic-based learning.